(untitled) (International Conference on Computers in Education, 2022)
What-If Hypothetical Implementations using Minecraft (WHIMC) is a set of Minecraft worlds that students can explore to learn more about astronomy, geosciences, and ecology. In this paper we present an attempt to analyze the game experience and STEM interest answers of students who played WHIMC as guided by instructions in custom teacher-created learning modules that incorporate its use. We describe the process of remodeling the game experience questionnaire of IJsselsteijn et al. (2013) and the STEM interest questionnaire of Lent et al. (2008) to fit the context of WHIMC. Open-ended questions were added to the GEQ to facilitate further interpretation of the GEQ answers. The GEQ was administered once (after playing WHIMC) and the SIQ was given twice (before and after playing WHIMC) both as outof-game tests. There was a noticeable neutrality in the SIQ answers of the low-performers, particularly in the dimensions of Self-Efficacy, Choice Goals and Outcome Expectation. The neutrality in the Self-Efficacy dimension shifted towards a higher degree of agreement in the post test. High-performing students showed consistently higher levels of agreement to the SIQ items compared to low-performers. In terms of the GEQ answers, the high- and low-performing groups share the same pattern of scores for each experience dimension. Low-performing students had higher scores in the Challenge dimension due to feeling time pressure. Open-ended answers showed that game- and learning-related WHIMC features were most liked, modulerelated difficulties were the most disliked, and game-related features were most instrumental to learning. High-performers reported that module-related aspects made the learning more difficult than it should be and low-performers said the technical bugs were the primary hurdles that made learning difficult.